FOSTERING CRITICAL THINKING IN MORAL EDUCATION IN MALAYSIAN SCHOOLS: A NEW LEARNING FRAMEWORK - Souad, Merah; Ramdane, Tahraoui (2016)
Most thinkers, educational practitioners, and parents acknowledge that schools are not only brickstructures, which role is traditionally of informationdispensing, but, rather, schools are ought to educate the students, and mold them into well-balanced social beings, who are active members of the society, and who dynamically interact with their environment. In other words, transforming the students into responsible ethical thinkers, who are characterized by good judgment in all that they do, in their relationships with others, and with themselves .(Mathew Lipman 1993) and this is the core business of moral education.